In vitro study of biofunctional indicators after exposure to asbestos-like fluoro-edenite fibres - Pugnaloni, A.; Lucarini, G.; Giantomassi, F.; Lombardo, L.; Capella, S.; Belluso, E.; Zizzi, A.; Panico, A.M.; Biagini, G.; Cardile, V. (Cellular and Molecular Biology, 2007)
The in vitro biological response to fluoro-edenite (FE) fibres, an asbestos-like amphibole, was evaluated in lung alveolar epithelial A549, mesothelial MeT-5A and monocyte-macrophage J774 cell lines. The mineral has been found in the vicinity of the town of Biancavilla (Catania, Sicily), where an abnormal incidence of mesothelioma has been documented. Cell motility, distribution of polymerized actin, and synthesis of vascular endothelial growth factor (VEGF) and of beta-catenin, critical parameters for tumour development, progression and survival, were investigated in A549 and MeT-5A cells exposed to 50 microg/ml FE fibres for 24 hr and 48 hr. The levels of cyclooxygenase (COX-2) and prostaglandin (PGE2), two molecules involved in cancer pathogenesis by affecting mitogenesis, cell adhesion, immune surveillance and apoptosis, were measured in J774 cells treated with FE fibres under the same experimental conditions. Finally, FE fibres were studied by SEM and EDS analysis to investigate their chemical composition. Exposure of A549 and MeT-5A cells to FE fibres affected differentially phalloidin-stained cytoplasmic F-actin networks, cell motility and VEGF and beta-catenin expression according to the different sensitivity of the two cell lines. In J774 cells it induced a significant increase in COX-2 expression, as assessed by Western blot analysis, and in the concentration of PGE2, measured in culture media by ELISA. SEM-EDS investigations demonstrated two types of FE fibres, edenite and fluoro-edenite, differing in chemical composition and both recognizable as calcic amphiboles. Fibre width ranged from less than 1 microm (prevalently 0.5 microm) to 2-3 microm (edenite) up to several microm (fluoro-edenite); length ranged from about 6 to 80 microm (edenite) up to some hundred microm (fluoro-edenite). Results provide convincing evidence that FE fibres are capable of inducing in vitro functional modifications in a number of parameters with crucial roles in cancer development and progression. Inhaled FE fibres have the potential to induce mesothelioma, even though their ability to penetrate lung alveoli depends on their aerodynamic diameter.